Does Diabetes Self Management Education (DSME) Have An Influence On The Quality of Life of Type 2 Diabetes Mellitus Patients? - Andri, Juli; Padila, Padila; Novitasari, Selvia; Ferasinta, Ferasinta; Andrianto, Muhammad Bagus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of diabetes self-management education (DSME) on the quality of life of patients with type 2 diabetes mellitus.This study used pre experimental design with one group pre and posttest with 15 respondents. The result analysis there were mostly 8 (53,3%) who were 56-70 years old, most of them were 14 (93,3%) female, mostly 8 (53,3%) Who had junior high school education, most of whom were 9 (60.0%) who 1-5 years suffering from diabetes, before DSME did the lowest quality of life score was 86 and the highest was 99, the average was 90.93, People after the DSME lowest life quality score was 88 and the highest was 105, the average was 98.67. The average quality of life after treatment has increased with the difference in the mean score of quality of life by using DSME (p = 0,000) in Bengkulu City Pasar Ikan Puskesmas Working Area. In Conclusion, There is an influence of Diabetes Self Management Education (DSME) on the quality of life of type 2 diabetes mellitus patients in the work area of ​​the Pasar Ikan Health Center, Bengkulu City. Keywords: Self Management Education (DSME), Quality of Life